Laparoscopic Bladder-Sparing Approach in Patients with Prostatic Rhabdomyosarcoma: A Case Series of Two Pediatric Patients - Ozden, Ender; Mercimek, Mehmet Necmettin; Sarikaya, Saban (Urology Journal, 2019)
Traditionally, the standard treatment of bladder-prostate rhabdomyosarcoma (BP-RMS) is being implemented to be total cystoprostatectomy and urinary diversion. However, current multimodal treatment approaches emphasize the importance of bladder-sparing surgery. In this case series, it was aimed to indicate the results of the laparoscopic bladder-sparing approach of two pediatric patients with BP RMS. They have admitted to the emergency department due to acute urinary retention (AUR). The tumors located in the prostate causing AUR were detected by Magnetic resonance imaging (MRI) and the pathological diagnosis was confirmed by biopsy. The patients were managed in a prosperous manner by implementing laparoscopic surgery with the cause of detection of a significant decrease in the size as well as the enhancement pattern of the tumors following neoadjuvant chemotherapy. No urinary incontinence, tumor recurrence or metastasis was observed at 36 and 28 months follow-up in case 1 and case 2, respectively. Laparoscopic bladder-sparing approaches may have an advantage in patients with BP RMS to decrease morbidity and mortality related to radical surgery. To our knowledge, these are the first cases of laparoscopic bladder-sparing approach in the treatment of pediatric prostate-derived embryonal RMS (PDERMS).